Status and advancement of microwave ablation in China. (3rd April 2017) - Yu, Jie; Liang, Ping
Abstract: Tumour ablation is defined as the direct application of chemical or thermal therapy to eradicate or substantially destroy a tumour. Currently, minimally invasive ablation techniques are available for the local destruction of focal tumours in multiple organ sites. Microwave ablation (MWA) is premised on the biological response of solid tumours to tissue hyperthermia, and it is a relatively low-risk procedure. Due to several advantages of MWA, including higher thermal efficiency, higher capability for coagulating blood vessels, faster ablation time and the simultaneous application of multiple antennae, MWA could be a promising minimally invasive ablation technique for the treatment of solid tumours. Therefore, the use of MWA has developed rapidly in China during the last decade. Many successful studies have been performed, and widespread use has been achieved for multiple types of tumours in China, especially for liver cancer. This review will describe the state-of-the-art of MWA in China, including the development of MWA equipment and its application in the treatment of multiple types of tumours.